Nudging the adoption of improved crop varieties: evidence from a large randomized controlled sweetpotato trial in Uganda - Okello, J.J.; Just, D.R.; Verschoor, A.; Ojwang, S.O.; Mutiso, J.M.; Mulwa, C.K.; Gong, C.; Namanda, S.; Rajendran, S.; Ssali, R.T.; Okim, M.; Campos, Hugo (2025)
To achieve agricultural transformation in developing countries in the face of challenges such as climate change, the use of improved crop varieties needs a jumpstart. Using a randomized controlled trial in Uganda, we test how the nudge theory can be harnessed to deliver increased adoption of improved sweet potato varieties. We find a 7% treatment effect, though the effect is not robust to alternative specifications. We find compelling evidence for heterogeneous treatment effects, with robust treatment effects among those who experienced a stronger emotional connection to the nudges that we deployed. A key concept to help explain this is nostalgia: farmers prone to nostalgia responded more strongly to the traditional farming imagery used to nudge the adoption of improved varieties.